Cluster Outer Points via Proximity Spaces - Almohammed, Raghad; Jabar, L. A. A. (Iraqi Journal of Science, 2024)
One of the most effective mathematical concepts for developing a clear picture of topological cluster proximity spaces is the follower points and the takeoff points. These are utilized in current study to construct three sets called the cluster outer set, the cluster disputed set and the cluster brim set denoted by , respectively. These three sets have divided the space into three separate pairs. On the other hand, the most important results, properties, and relationships between the sets were highlighted and studied.